2018
DOI: 10.1177/0038038518765559
|View full text |Cite
|
Sign up to set email alerts
|

Kρίση and Μετανάστευση in Greece: From Illegal Migrants to Refugees

Abstract: In this essay I outline the ways in which κρίση ( krísi – crisis) and μετανάστευση ( metanástefsi – migration) have been interrelated during the last decade in Greece. By being grounded in concrete times and places, I argue that these interrelations, far from being stable and fixed, take their form and meaning within wider social, economic and political contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
0
11
0
Order By: Relevance
“…While we cannot directly test these arguments with our data, the high support for helping refugees in the two Mediterranean countries seems a good test case, given their dire economic situation and the high influx of refugees. For Greece, Lafazani (2018) argues that the discourse on migrants has shifted during the massive inflow of refugees in 2015. The desperate situation of refugees, the mass-drowning of women and children and the widespread spontaneous local help coincided with the election of the pro-migrant Syriza government in 2016, leading to a widespread perception of forced migrants as deserving humans in need (Lafazani 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot directly test these arguments with our data, the high support for helping refugees in the two Mediterranean countries seems a good test case, given their dire economic situation and the high influx of refugees. For Greece, Lafazani (2018) argues that the discourse on migrants has shifted during the massive inflow of refugees in 2015. The desperate situation of refugees, the mass-drowning of women and children and the widespread spontaneous local help coincided with the election of the pro-migrant Syriza government in 2016, leading to a widespread perception of forced migrants as deserving humans in need (Lafazani 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As Athanasiou and Tsimouris (2013) write, the nationalised, possessive, white and heteronormative masculinity is incorporated as the cultural norm that regulates the contents of the human and the political. A norm which is The Significance of the Insignificant manufactured within multiple and interlocking scales across the borderline: the Eurodac system and the Dublin regulation (Tsianos and Kuster 2016); the building of the wall in the Evros border region and the opening of new detention centres in the Aegean (Grigoriadis and Dilek 2019); the advertising of the numbers of deportations and arrests by the Xenios Zeus police operation (Dalakoglou 2013); the TV news overflowing with words such as "illegality" and "criminality" while what one can actually see on the screen are three alleged migrants simply walking in the street (Lafazani 2018b); the daily pogroms, attacks and assaults against migrants, women and LGBTQI people in the centre of the city, for which usually no one gets charged or even arrested (Tsimouris 2014).…”
Section: Act 2: Public Spaces or Rejection And Acceptancementioning
confidence: 99%
“…Harsh and discriminatory policies were implemented (Dalakoglou 2013;Karamanidou 2016), while the ultra-right grew aggressively (Brekke 2014;Kandylis and Kavoulakos 2011). The invisibility of the previous period was transformed in a hyper-visibility, with hundreds of newspaper articles and TV reports presenting Athens as a dangerous city due to the presence of "illegals" (Lafazani 2018b). Within this context, and as my own research clearly showed, Athens became a more hostile city for migrants.…”
mentioning
confidence: 91%
“…Moreover, in 2011 a successfully organised solidarity campaign for 300 migrant workers took place, initiating a hunger strike that claimed migrants' legalisation and equal political and social rights to Greek workers (Pistikos, 2016). Finally, during the long refugee summer of 2015, a wide social solidarity movement with multiple acts of hospitality surfaced (Lafazani, 2018a) resulting in several building squats that operated as refugee housing projects in Athens, Thessaloniki, and Mytilene (Agustín & Jørgensen, 2019;Raimondi, 2019;Squire, 2018). Finally, in the summer of 2016, after the evacuation of the makeshift refugee settlement in Idomeni, on the border with North Macedonia, locals, refugees and international activists organised a transnational No Border Camp in Thessaloniki (Tsavdaroglou, 2019).…”
Section: Introductionmentioning
confidence: 99%